Dynamics in diagnoses and pharmacotherapy before and after diagnosing idiopathic pulmonary fibrosis - Davidsen, Jesper Rømhild (ERJ Open Res, 2020)
BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is a well-characterised interstitial lung disease. Typically, IPF diagnosis is delayed due to nonspecific symptoms, but can also be delayed due to treatment attempts on false indication or due to treatment targeting common comorbidities. This observational study aimed to assess the dynamics in the medication and diagnosis patterns in the period before and after an IPF diagnosis. METHODS: We identified all Danish patients with IPF between 2002 and 2017. We evaluated new and ongoing drug treatments and incident diagnoses 36 months before and 12 months after an IPF diagnosis by use of Danish nationwide registries. To aid interpretation, 10 random controls were recruited for each case. RESULTS: A total of 650 IPF patients were identified (median age 73 years (interquartile range 65–78), 70.3% males). Prior to the IPF diagnosis, the most prevalent diagnoses were dyspnoea and non-IPF interstitial lung diseases. For drug use, IPF patients had higher initiation rates for antibiotics, oral corticosteroids and mucolytics. In terms of drug volume, IPF patients used more respiratory drugs, antibiotics, immunosuppressants, corticosteroids, proton pump inhibitors, benzodiazepines and opium alkaloids within the 6 months preceding their IPF diagnosis, compared to the controls. Overall drug use decreased after an IPF diagnosis, mainly due to a reduced glucocorticoid and cardiovascular drug use. CONCLUSION: Among IPF patients, an increased drug use was observed for diagnoses with symptoms overlapping those of IPF, particularly this was observed during the last 6 months before an IPF diagnosis. This emphasises the need for an increased IPF awareness.